2021
DOI: 10.1038/s41467-021-21231-2
|View full text |Cite
|
Sign up to set email alerts
|

A superconducting switch actuated by injection of high-energy electrons

Abstract: Recent experiments with metallic nanowires devices seem to indicate that superconductivity can be controlled by the application of electric fields. In such experiments, critical currents are tuned and eventually suppressed by relatively small voltages applied to nearby gate electrodes, at odds with current understanding of electrostatic screening in metals. We investigate the impact of gate voltages on superconductivity in similar metal nanowires. Varying materials and device geometries, we study the physical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 31 publications
18
79
1
Order By: Relevance
“…We first discuss the response of device A1 to a side-gate voltage V G1 , similar to previous work 1,9,11 . The electric-field distribution in this configuration was calculated using three-dimensional (3D) finite element simulations (Methods).…”
Section: Critical Current Suppression and Electric Fieldsmentioning
confidence: 84%
See 1 more Smart Citation
“…We first discuss the response of device A1 to a side-gate voltage V G1 , similar to previous work 1,9,11 . The electric-field distribution in this configuration was calculated using three-dimensional (3D) finite element simulations (Methods).…”
Section: Critical Current Suppression and Electric Fieldsmentioning
confidence: 84%
“…The large difference between I C and I R indicates substantial self-heating in the normal state, together with limited heat extraction via the leads or the substrate, typical of metallic nanowires 14,15 . Further details on sample fabrication and basic characterization are reported in another study 9 and in Methods. Here we present the results from four devices, referred to as devices A1, A2, B and C. Extended data and three additional devices, used as references, are shown in more detail in Supplementary Figs.…”
Section: Critical Current Suppression and Electric Fieldsmentioning
confidence: 99%
“…A theoretical model based on the Ginzburg–Landau theory is proposed here, appropriately explaining the experimental data. Accounting for the effect of the squeezing of the supercurrent by the electric field, it adds further insight to the puzzling origin of the phenomenon, which has been investigated in different geometries and other materials, and is subjected to controversy at the present time 7 , 9 , 16 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The microscopical justification for the occurrence of this effect, which cannot be justified in the Barden–Cooper–Schrieffer (BCS) framework, is not fully accounted for at the present time and is the subject of an unsettled debate 13 15 , with separate intrinsic and extrinsic effects potentially contributing in various geometries and in different superconducting materials. Ritter et al 16 ascribe the critical current quenching observed in titanium nitride nanowires to the injection of energetic electrons from the gate electrodes to the superconductor, which trigger the formation of a large number of quasiparticles that drive the nanowire back to the normal state. Alegria et al 17 and Golokolenov et al 18 support similar arguments to account for the behavior observed in electron tunneling spectroscopy experiments in titanium nanowires and in a vanadium waveguide resonator, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works show GCS in thin metallic nanowires, 12 , 18 , 22 , 23 in proximitized normal metal in a superconductor–normal–superconductor (SNS) junction 13 and in Dayem nanobridges. 15 , 17 , 20 In addition to high-speed superconducting switches, 23 observation of GCS in superconducting nanostructures led to the realization of new nanodevices such as gate-controlled superconducting phase shifter 16 and half-wave nanorectifiers. 20 Despite the clear advantages of GCS for applications, the origin of the effect is still under debate.…”
Section: Introductionmentioning
confidence: 96%